New Chairs Boot Camp - Margaret A Thomas-Evans; Chera A LaForge; Katie Chaney (Academic Chairpersons Conference Proceedings, 2020)
Many chairs take on their role without any formal training, which leads to frustration and dissatisfaction. We developed a boot camp to provide initial onboarding and orientation for new chairs. In this session, we provide an overview of our program, which focused on strategic enrollment management and department administration.
Keywords: New chairs training; department management; strategic enrollment